Formation of Short-Chain Fatty Acids, Excretion of Anthocyanins, and Microbial Diversity in Rats Fed Blackcurrants, Blackberries, and Raspberries - Greta Jakobsdottir; Narda Blanco; Jie Xu; Siv Ahrné; Göran Molin; Olov Sterner; Margareta Nyman (Journal of Nutrition and Metabolism)
Introduction. Berries contain high amounts of dietary fibre and flavonoids and have been associated with improved metabolic health. The mechanisms are not clear but the formation of SCFAs, especially propionic and butyric acids, could be important. The potent antioxidant and antimicrobial properties of flavonoids could also be a factor, but little is known about their fate in the gastrointestinal tract. Aim. To compare how blackcurrants, blackberries, raspberries, and Lactobacillus plantarum HEAL19 affect formation of SCFAs, inflammatory status, caecal microbial diversity, and flavonoids. Results and Conclusions. Degradation of the dietary fibre, formation of SCFAs including propionic and butyric acids, the weight of the caecal content and tissue, and the faecal wet and dry weight were all higher in rats fed blackcurrants rather than blackberries or raspberries. However, the microbial diversity of the gut microbiota was higher in rats fed raspberries. The high content of soluble fibre in blackcurrants and the high proportion of mannose-containing polymers might explain these effects. Anthocyanins could only be detected in urine of rats fed blackcurrants, and the excretion was lower with HEAL19. No anthocyanins or anthocyanidins were detected in caecal content or blood. This may indicate uptake in the stomach or small intestine.